Analysis Theories Leadership Styles for Millennial Generation - Gigih Afriadhi Permana*; Anis Eliyana (Riwayat: Educational Journal of History and Humanities, 2023)
Currently, the company's employees have begun to shift from the older generation to the millennial generation, which has a style and characteristics that are very different from the previous generation, which are selfish but very reliable in terms of technology. Companies must quickly adapt and apply appropriate leadership style techniques to achieve optimal company performance amidst the domination of millennial generation employees. By paying attention to the development of an increasingly modern era, of course, the development of knowledge needs to be developed in order to achieve targets. This article aims to identify effective leadership styles in dealing with millennial generation employees by considering various current leadership theories in the context of workforce turnover. This study used a systematic literature review. Furthermore, it explores the strengths and weaknesses of various leadership styles for millennial employees to understand the appropriate leadership style for millennials. The conclusion shows that a combination of the five leadership style approaches is needed to accommodate millennial characteristics that are different from the previous generation with namescivilized innovation leadership approach.